2022
DOI: 10.1017/s0047404522000240
|View full text |Cite
|
Sign up to set email alerts
|

Context, precision, and social perception: A sociopragmatic study

Abstract: In two perception experiments we explore the social indexicality of numerical expressions, comparing the evaluation of three variants: precise (e.g. ‘forty-nine minutes’) vs. explicitly approximate (e.g. ‘about fifty minutes’) vs. underspecified (e.g. ‘fifty minutes’). We ask two questions: (i) What constellations of social meanings are associated with each of these variants? (ii) How are such indexical associations modulated by the conversational setting? We find that the choice of approximate vs. precise for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…As discussed in §1, scholars of language across different traditions have long submitted to the view that communication simultaneously involves referential and indexical signs, "one working in conjunction with the other" (Gumperz & Cook-Gumperz 2007); and that the interpretation of descriptive meaning cannot be conceived of independently of the social context (Silverstein 1985;Ochs 1992;Eckert 2019;Cook-Gumperz 1992). In a similar vein, a recent line of work at the interface of pragmatics and sociolinguistics showed that social meanings are productively and systematically inferred from the semantic properties of speech across a variety of linguistic expressions (Acton & Potts 2014;Acton 2019;Beltrama & Staum Casasanto 2017;Beltrama et al 2022;Glass 2015;Jeong 2021;Hunt & Acton 2022; see §1 for further details), motivating a view in which different dimensions of meaning cannot be seen as independent from one another. Against this background, the persona effects observed in our study make it possible to take a further step towards building a bridge between sociolinguistic and more abstract, reference-oriented approaches to the study of meaning, questioning the exclusion of identity considerations from pragmatic reasoning that has been tacitly advocated in much work in semantics and analytic philosophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in §1, scholars of language across different traditions have long submitted to the view that communication simultaneously involves referential and indexical signs, "one working in conjunction with the other" (Gumperz & Cook-Gumperz 2007); and that the interpretation of descriptive meaning cannot be conceived of independently of the social context (Silverstein 1985;Ochs 1992;Eckert 2019;Cook-Gumperz 1992). In a similar vein, a recent line of work at the interface of pragmatics and sociolinguistics showed that social meanings are productively and systematically inferred from the semantic properties of speech across a variety of linguistic expressions (Acton & Potts 2014;Acton 2019;Beltrama & Staum Casasanto 2017;Beltrama et al 2022;Glass 2015;Jeong 2021;Hunt & Acton 2022; see §1 for further details), motivating a view in which different dimensions of meaning cannot be seen as independent from one another. Against this background, the persona effects observed in our study make it possible to take a further step towards building a bridge between sociolinguistic and more abstract, reference-oriented approaches to the study of meaning, questioning the exclusion of identity considerations from pragmatic reasoning that has been tacitly advocated in much work in semantics and analytic philosophy.…”
Section: Discussionmentioning
confidence: 99%
“…The second property is that variation in precision is socially meaningful. In particular, speakers using sharp numbers (e.g., 203) -normally taken to signal a high level of precision -are perceived as embodying social qualities pertaining to high status and intellectual standing -e.g., being articulate, intelligent, educated, hard-working -as well as low solidarity and likabilitye.g., annoying, pedantic, obsessive, and uptight; conversely, speakers using numerals in an explicitly imprecise fashion (i.e., "approximately 200") have been shown to be perceived as embodying opposite sets of qualities -e.g., likable, laid-back, friendly-and in a way that is remarkably robust across conversational contexts (Beltrama 2018;Beltrama et al 2022). This suggests that different levels of precision are taken by comprehenders to index distinct constellations of socio-indexical information, similar to what happens with countless other examples of linguistic variation.…”
Section: Introductionmentioning
confidence: 98%
“…Project A05 complements these studies on the effects of speaker role with studies on how the choice of precision level in context affects perceptions of the speaker (Beltrama et al, 2022 ). In a series of internet-based studies, we extend the matched guise technique (Campbell-Kibler, 2010 ; Beltrama, 2018 ) to the investigation of register, by varying not only the linguistic forms tested (e.g., the trip to the airport takes 49/50/about 50 min) but also the situational contexts in which they are used.…”
Section: Experimental Approaches: Isolating Intra-individual Variabilitymentioning
confidence: 99%
“…On the one hand, it has been shown that listeners reason rely on precision as a cue to draw social inferences about speaker. For example, speakers using sharp numbers (e.g., "207") -normally taken to signal a high level of precision (Krifka 2007) -are associated with a cluster of social qualities that can be traced back to two core dimensions of social evaluation: high intellectual status -e.g., as articulate, educated, intelligent; and low sociability -e.g., as annoying, pedantic, obsessive (Beltrama 2018;Beltrama, Solt & Burnett 2022). 3 Similarly, speakers using numerals in an explicitly imprecise fashion (i.e., "around 200") are perceived as embodying opposite sets of qualities -e.g., as friendlier and more laid-back, but less intelligent and educated (Beltrama et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, speakers using sharp numbers (e.g., "207") -normally taken to signal a high level of precision (Krifka 2007) -are associated with a cluster of social qualities that can be traced back to two core dimensions of social evaluation: high intellectual status -e.g., as articulate, educated, intelligent; and low sociability -e.g., as annoying, pedantic, obsessive (Beltrama 2018;Beltrama, Solt & Burnett 2022). 3 Similarly, speakers using numerals in an explicitly imprecise fashion (i.e., "around 200") are perceived as embodying opposite sets of qualities -e.g., as friendlier and more laid-back, but less intelligent and educated (Beltrama et al 2022). On the other hand, and more centrally for our purposes, it's been shown that the social information available in the context affects the computation of the level of precision with which a numeral is interpreted.…”
Section: Introductionmentioning
confidence: 99%